Studi Kelayakan Bisnis Pengembangan Inovasi Varian Rasa Bakso Aci Pada Badan Usaha Tercabaikan - Darsiti Darsiti; Asep Mahmudin; Cahya Putri Julyandaru; Putri Meilani Gustian; Salsa Sabila (Pusat Riset dan Inovasi Nasional, 2024)
Tercabaikan is one of the MSMEs in the city of Bandung, West Java, which innovates the taste of Bakso Aci into a flavor that is favored by many people. Tercabaikan Company was first initiated by Mr. Inggra Dwipo Prayogo as the owner at this time in 2018 which is located at Jl. Sukagalih number 193 RT 05 / RW 06 Pasirjati Ujungberung, Bandung City, West Java. The purpose of this study was to test the feasibility of neglected business entities by adding variations to existing product flavors. Descriptive method, the techniques used are interviews and field observations on March 15, 2023. The results of this study indicate that the Tercabaikan business entity has the potential to be feasible to develop with innovation in Bakso Aci products. The feasibility analysis shows business sustainability with positive profit projections. However, it is important to continue to monitor and evaluate financial performance in accordance with the projections that have been generated. The feasibility results determined on this neglected business entity through a series of comprehensive observations carried out to obtain a feasible conclusion, especially in the financial elements of the neglected business entity.